2009
DOI: 10.1002/eji.200939814
|View full text |Cite
|
Sign up to set email alerts
|

Shifting therapeutic attention in MS to osteopontin, type 1 and type 2 IFN

Abstract: It is widely debated whether MS is mediated solely by Th1, or solely by Th17, whether it might be mediated by both pathways, or perhaps by neither pathway. We must integrate the following four facts: first, MS lesions have a signature of IL-6-, IL-17-, osteopontin-and IFN-driven transcriptional activity. Second, MS is worsened with administration of IFN-c, the quintessential type 2 IFN and Th1 cytokine. Third, blockade of TNF-a worsened MS in clinical trials. Fourth, inhibiting the main driver of Th17, IL-23, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Research on EAE demonstrated that both IFN-g-producing Th1 and IL-17-producing Th17 cells could cause inflammatory pathology in the CNS (9,10). Although characterization of pathogenic T cells in EAE has ignited a search for similar cells in humans, the identity of pathogenic T cells in MS has not been established (10).…”
Section: Ultiple Sclerosis (Ms) Is An Inflammatory Demyelinating DImentioning
confidence: 99%
See 1 more Smart Citation
“…Research on EAE demonstrated that both IFN-g-producing Th1 and IL-17-producing Th17 cells could cause inflammatory pathology in the CNS (9,10). Although characterization of pathogenic T cells in EAE has ignited a search for similar cells in humans, the identity of pathogenic T cells in MS has not been established (10).…”
Section: Ultiple Sclerosis (Ms) Is An Inflammatory Demyelinating DImentioning
confidence: 99%
“…In addition, increasing evidence suggest a pathogenic role for cytotoxic effector T cells in MS (14,15). Moreover, a recent clinical trial of anti-IL12p40 Ab to block IL-12/IL-23 signaling failed to modulate MS (16), making it difficult to portray a complete picture of MS (9).…”
Section: Ultiple Sclerosis (Ms) Is An Inflammatory Demyelinating DImentioning
confidence: 99%
“…In EAE, decreased OPN production by IFNb treatment contributes to the reduced migratory activity of T cells. 39 Thus, although OPN might not be a specific marker for MS, targeting it might present a therapeutic approach to MS. 67,68 Further studies will be needed to validate this hypothesis.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, it is one of the most abundant gene transcripts within acute MS lesions (Chabas et al, 2001) and is also elevated in plasma around the time of relapse (Steinman, 2009a). Studies showed that the VLA-4 integrin binds to OPN, thus increased levels of OPN within lesions could attract VLA-4-carrying cells (Steinman, 2009a).…”
Section: Alterations In Numerous Intercellular Signalingmentioning
confidence: 99%